2022
DOI: 10.3343/alm.2022.42.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Laboratory Data Analysis to Predict the Clinical Severity of Coronavirus Disease 2019 in 1,952 Patients in Daegu, Korea

Abstract: Background: Laboratory parameter abnormalities are commonly observed in COVID-19 patients; however, their clinical significance remains controversial. We assessed the prevalence, characteristics, and clinical impact of laboratory parameters in COVID-19 patients hospitalized in Daegu, Korea. Methods:We investigated the clinical and laboratory parameters of 1,952 COVID-19 patients on admission in nine hospitals in Daegu, Korea. The average patient age was 58.1 years, and 700 (35.9%) patients were men. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
2
22
2
Order By: Relevance
“…Moreover, the severity of COVID‐19 cases are related to respiratory insufficiency or acute respiratory distress syndrome (indicator: low O 2 saturation); coagulopathies (indicator: elevated D‐dimer, prothrombin time prolongation); inflammation (indicator: elevated CRP (an indicator of active acute inflammation), IL‐6); multi‐organ damage: liver damage (indicator: hypoalbuminemia), and lymphopenia. 3 , 72 , 135 Thus, these symptoms can be reduced by Mg 2+ supplementation. For instance, it has been observed that concomitant supplementation of vitamin D, vitamin B12, and Mg 2+ in COVID‐19 patients can decrease ICU admission incidence and O 2 therapy requirements.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 99%
“…Moreover, the severity of COVID‐19 cases are related to respiratory insufficiency or acute respiratory distress syndrome (indicator: low O 2 saturation); coagulopathies (indicator: elevated D‐dimer, prothrombin time prolongation); inflammation (indicator: elevated CRP (an indicator of active acute inflammation), IL‐6); multi‐organ damage: liver damage (indicator: hypoalbuminemia), and lymphopenia. 3 , 72 , 135 Thus, these symptoms can be reduced by Mg 2+ supplementation. For instance, it has been observed that concomitant supplementation of vitamin D, vitamin B12, and Mg 2+ in COVID‐19 patients can decrease ICU admission incidence and O 2 therapy requirements.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 99%
“…In severe cases, particularly in the elderly, the virus can interact with the immune system to induce an excessive innate immune response, or even a cytokine storm, which can disrupt the epithelial cells in the lung and the gas-blood barrier, leading to the acute respiratory distress syndrome (ARDS). At the same time, the virus also attacks lymph tissue and then causes lymphopenia that prevents the virus from clearance ( 48 50 ). Correspondingly, relative lymphopenia, cytokine storm, and multiple organ failure become significant indicators of COVID-19 severity and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ]. Yoo et al showed that the hypoalbuminemia and abnormal AST levels were prominent in severe COVID-19 patients, and abnormal albumin levels were strongly correlated with COVID-19 severity with 78% of patients in the severe group having hypoalbuminemia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory parameters may be more objective than clinical parameters in evaluating the patient’s condition. It has been reported that abnormal levels of laboratory markers such as C-reactive protein (CRP), D-dimer, lactate dehydrogenase (LDH), interleukin (IL)-6, and fibrinogen correlate with disease severity [ [13] , [14] , [15] , [16] ]. To date, the relationship between clinical severity and disease progression in different age groups is unclear.…”
Section: Introductionmentioning
confidence: 99%